Enhancing Early Second Language Acquisition through Parent-teacher Practices - Muhammad Haikal; Fahrul Rozi (Universitas Ahmad Dahlan, 2022)
The phenomenon of the second language has been widely spread which demands many parents to let their children learn as early as possible. Parents and teachers are the two stakeholders who are able to grant this idea. This study was conducted to present teachers’ and parents’ practices in teaching and/or introducing English as a second language and see whether or not the two perspectives were in line. The phenomenology of the qualitative study was employed in this study by using the interview as the research instrument, and two teachers were chosen as the research participants. Therefore, the data analysis of this research was conducted by transcribing the interview, open-coding, analytical coding, axial coding, and selective coding, and emerging the theme of the coding. In addition, the researcher found several findings related to early second language acquisition through parent-teacher practices such as language exposure, language accuracy, encouragement of parent-child interaction, fun learning to foster motivation of language learning, realia teaching aid, reward presentation, and the use of video after completing the data analysis by coding.